2009
DOI: 10.1073/pnas.0909597107
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton-based forecasting of stem cell lineage fates

Abstract: Stem cells that adopt distinct lineages cannot be distinguished based on traditional cell shape. This study reports that higher-order variations in cell shape and cytoskeletal organization that occur within hours of stimulation forecast the lineage commitment fates of human mesenchymal stem cells (hMSCs). The unique approach captures numerous early (24 h), quantitative features of actin fluororeporter shapes, intensities, textures, and spatial distributions (collectively termed morphometric descriptors). The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
249
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(253 citation statements)
references
References 29 publications
4
249
0
Order By: Relevance
“…Other mechanical cues correlated with fate commitment of mesenchymal stem cells are cell shape and the mean stress in the cytoskeleton (15). Because actin transfers physical cues between the cell exterior and interior, it likely plays a major role in stem cell linage commitment (14,25). However, there have been no measurements available on the forces in specific structural proteins in adult cell reprogramming and dedifferentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Other mechanical cues correlated with fate commitment of mesenchymal stem cells are cell shape and the mean stress in the cytoskeleton (15). Because actin transfers physical cues between the cell exterior and interior, it likely plays a major role in stem cell linage commitment (14,25). However, there have been no measurements available on the forces in specific structural proteins in adult cell reprogramming and dedifferentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Using high-content imaging of MSCs following IFN-γ stimulation, morphological features were identified that significantly correlated with immunosuppressive capacity and predicted the immunosuppressive capacity of other MSC and non-MSC lines, as well as the effects of IFN-γ pretreatment on immunosuppressive capacity. These findings highlight MSC morphology as an attribute associated with immunosuppressive capacity and provide additional evidence that morphological profiling can be used to predict MSC in vitro function (12,(15)(16)(17). …”
mentioning
confidence: 95%
“…Morphology has been identified in many studies as a predictive marker of osteogenic capacity (15,16); however, limited research exists that demonstrates a correlation of morphology with other MSC functions such as immunosuppression. Further improvement on the methods for morphological assessment and applicability across multiple donors is necessary to fully demonstrate its possible utility as a predictor of not only in vitro but also in vivo MSC immunosuppressive capacity.…”
Section: Morphological Features Of Mscs After Ifn-γ Stimulation Corrementioning
confidence: 99%
“…5,6 Toward this end, use of biomaterials may provide a way to recreate these 3D environments, while allowing the study of complex cellular interactions. This includes the application of methods for high-throughput, multivariate analyses of highcontent data (e.g., from gene microarrays, suspension arrays, time-of-flight-mass spectrometry, and microscopy images) [7][8][9][10][11] that yield system-level information of complex cellular processes at or close to a single-cell level. However, innovative strategies that more closely mimic in vivo microenvironments need to be further coupled with the sophisticated methods outlined above.…”
Section: Introductionmentioning
confidence: 99%